Red Raspberry (Rubus idaeus L.) Seed Oil: A Review - Ispiryan, Audronė (Plants (Basel), 2021)
Raspberry (Rubus idaeus L.) seed oil (RSO) is considered as a source of high value bioactive compounds as fatty acids, tocopherols, tocotrienols, carotenoids, flavonoids, phytosterols, antioxidants, monoterpenes and many other chemical constituents. These compounds are appreciated as a source of nutrition for humans, as additives in cosmetic production, has immense therapeutic potential. Raspberry seed oil exerts many pharmacological effects included antimicrobial, antioxidant, anti-inflammatory activity and many other effects. The various databases like PubMed and Science Direct were used to identify, analyze and summarize the research literature on raspberries. This review will highlight recent developments of the chemical constituents and nutraceutical and cosmetical effects of RSO. Practical application: analyzed recent researches and international patents containing raspberry seed oil can help practitioners of various industries create new high-value products.